2020
DOI: 10.2174/2211352517666190528114041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant, Antibacterial, Cytotoxicity, and Hemolyses Activity of Essential Oils from Flower of Matricaria chamomilla var. Chamomilla

Abstract: Objective: To report the chemical composition and bioactivity (including antioxidantand antimicrobial activity, hemolytic activities, and cytotoxicity) of flowers essential oil from Matricariachamomillavar. chamomilla(MCCO) for the first time. Methods: The essential oil was obtained using a Clevenger-type apparatus. Then, the essential oils composition was identified by chromatography methods. DPPH radical scavenging activity (RSA), β-carotene bleaching (BCB), and ferrous ion chelating ability (FIC) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…26 Therefore, MAH offers many advantages, such as lower energy costs, shorter extraction time and it is a cleaner method because it is not based on solvents and doesn't generate residues. 27 Studies that have been carried out with different research projects have revealed that our yield rate is higher than that of Hajjaj et al 28 who have obtained a yield of 0.4%, and lower than that of Kazemi 29 who has obtained a yield of 0.82% and Mahdavi et al 30 who has achieved a yield of 1.27%. The difference in yield, especially with the results of Mahdavi et al 30 is explained by the fact that the EOs were extracted from the flowers.…”
Section: Resultsmentioning
confidence: 51%
“…26 Therefore, MAH offers many advantages, such as lower energy costs, shorter extraction time and it is a cleaner method because it is not based on solvents and doesn't generate residues. 27 Studies that have been carried out with different research projects have revealed that our yield rate is higher than that of Hajjaj et al 28 who have obtained a yield of 0.4%, and lower than that of Kazemi 29 who has obtained a yield of 0.82% and Mahdavi et al 30 who has achieved a yield of 1.27%. The difference in yield, especially with the results of Mahdavi et al 30 is explained by the fact that the EOs were extracted from the flowers.…”
Section: Resultsmentioning
confidence: 51%
“…The activity of the natural positive control is higher in all the tests; however, if values described in the scientific literature for known essential oils, such as chamomile [ 42 ], cinnamon [ 43 ], and Rosmarinus [ 44 ], are analyzed, the results are quite interesting. Comparing this research with another carried out in Venezuela, the results are quite similar for common bacteria: Staphylococcus aureus (7.921 mg/mL research in Ecuador and 6.250 mg/mL research in Venezuela); Enterococcus faecalis (5.540 mg/mL research in Ecuador and 3.125 mg/mL research in Venezuela); Escherichia coli (6.250 mg/mL research in Ecuador and 6.250 mg/mL research in Venezuela), and Pseudomonas aeruginosa (8.38 mg/mL research in Ecuador and 3.125 mg/mL research in Venezuela) [ 45 ]. Bioautography evidences the antimicrobial activity of caryophyllene; there is ample evidence of its action on this molecule, such as that performed on P. gingivalis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this test, M. chamomilla EOs showed the highest DPPH scavenging activity after 90 min of reaction [107]. On the other hand, M. chamomilla EOs had less activity than the used standards BHT and α-tocopherol in both DPPH and β-carotene bleaching tests, while it showed a comparable ferrous ion chelating ability than the citric acid standard [108]. The ABTS test was used to investigate the antioxidant power of EOs obtained by different extraction techniques (steam stripping, hydrodistillation, steam-dragging distillation with simultaneous steam extraction using an organic solvent, maceration, and supercritical fluid extraction) [109].…”
Section: Pharmacological Interest 41 Antioxidant Activitymentioning
confidence: 92%
“…The results showed that the EO was more active against S. aureus MRSA compared to reference strains. On the other hand, P. aeruginosa was the most sensitive bacteria in both diffusion and micro-dilution assays [108,111], showing that Gram-negative bacteria could be more sensitive to EO compared to Gram-positive strains. In addition, Shakya et al [130] found that M. chamomilla flower EO significantly reduced Enterococcus faecalis growth.…”
Section: Antibacterial Activitymentioning
confidence: 99%